Latent classes and related predictors of demand for home-and community-based integrated care for older Chinese adults - Wang, Zhenyu; Liu, Zhihan (Frontiers in Public Health, 2023)
Background Home-and community-based integrated care has been developing rapidly in China in recent years. However, empirical research on the demand from older people is insufficient. Most studies have failed to identify or differentiate the heterogeneity of older people, resulting in poor understanding of their needs and fragmentation of services. This study seeks to identify latent classes of demand for home-and community-based integrated care among older Chinese adults and the predictors that differentiate these demands. Methods From January to March 2021, a questionnaire was administered to older people (aged ≥60 years) in community-based service centers for older people in six districts of Changsha City, Hunan Province. Participants were selected through purposive and incidental sampling. Latent profile analysis was used to categorize older people’s demand for home-and community-based integrated care. By extending Andersen’s behavioral model of health service use, and running multinomial logistic regression analyses, we explored which factors influenced the latent classes of demand. Results A total of 382 older people were included in the analyses: 64.4% were women and 33.5% were aged 80–89. The demand from older people for home-and community-based integrated care was classified into four latent classes: high health and social interaction demand (30% – 115/382); high comprehensive demand (23% – 88/382); high care service demand (26% – 100/382), and high social participation and low care demand (21% – 79/382). Taking this last class as the reference group, the other three latent classes differed significantly in the factors of predisposition, enabling, need, and perception of aging. Conclusion The demand from older people for home-and community-based integrated care is multifaceted and heterogeneous. Services for older people should be designed with different sub-models of integrated care.